TRADISI BERBURU BABI PADA MASYARAKAT NAGARI LIMBANANG DI KECAMATAN SULIKI KABUPATEN LIMA PULUH KOTA - Nanda Afridal Putra; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The tradition of hunting pigs is an activity carried out by the people in Nagari Limbanang. This tradition is carried out every week with different implementing areas. This tradition is a physical activity that uses hunting dogs as their main weapon. These dogs are dogs that have been trained in hunting pigs. The research entitled "The Tradition of Hunting Pig in Nagari Limbanang Communities in Suliki District, Lima Puluh Kota Regency", this paper is the result of in-depth research on the implementation processes of the tradition of hunting pigs in Nagari Limbanang, the meaning contained in the hunting tradition, as well as the benefits that can be obtained from implementing the tradition of hunting pigs. This research uses qualitative research methods with purposive sampling technique. The data in this study were obtained through direct observation and interviews from predetermined informants, such as principal, non-farmer hunters, hunters from a farmer background and young hunters. The results showed that the tradition of hunting pigs was carried out to assist farmers in eradicating wild boar pests that often bother them. There are several processes that hunters will go through in carrying out this tradition of hunting pigs, such as the initial process, the process when hunting, and the process after hunting. The meanings contained in the traditions also vary, all depending on the way the hunter views the tradition of hunting pigs. Likewise with the benefits that will be obtained, everything returns to the hunter's perspective on the tradition of hunting pigs, there are material benefits and non-material benefits.    Key words: Tradition, hog hunting, hunter